Identification of key taste components in loquat using widely targeted metabolomics. (1st September 2020) - Zou, Shicheng; Wu, Jincheng; Shahid, Muhammad Qasim; He, Yehua; Lin, Shunquan; Liu, Zhenhua; Yang, Xianghui
Highlights: A total of 536 metabolites were identified from the fruits of two loquat cultivars. 193 metabolites were differentially accumulated between two cultivars. Variations in carbohydrates, organic acids, amino acids and phenolics cause taste difference. Results provide new insights about metabolic causes of taste variation in loquat. Abstract: Loquats can be divided into white- and yellow-fleshed cultivars. Generally, white-fleshed cultivars taste better than yellow-fleshed cultivars. Currently, metabolic causes of differences in taste are unknown, due to the lack of a large-scale and comprehensive investigation of metabolites in loquat fruit. Here, we performed a LC-MS/MS-based widely targeted metabolome analysis on two cultivars, 'Baiyu' (white-fleshed) and 'ZaozhongNo. 6' (yellow-fleshed). A total of 536 metabolites were identified, 193 of which (including 7 carbohydrates, 12 organic acids and 8 amino acids) were different between the cultivars. Pathway enrichment analysis also identified significant differences in phenolic pathways between the cultivars. Our results suggest that taste differences between the cultivars can be explained by variations in composition and abundance of carbohydrates, organic acids, amino acids, and phenolics. This study provides new insights into the underlying metabolic causes of taste variation in loquat.